PENURUNAN KADAR TANIN DAN ASAM FITAT PADA TEPUNG SORGUM MELALUI FERMENTASI Rhizopus oligosporus, Lactobacillus plantarum dan Saccharomyces cerevisiae - Raden Haryo Bimo Setiarto; Nunuk Widhyastuti (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Problems in using sorghum flour as food material was the presence of tannin and phytic acid that can reduce nutritition quality of sorghum flour. This study aimed to analyze the influence of Rhizopus oligosporus, Lactobacillus plantarum and Saccharomyces cerevisiae fermentation on the reduction levels of tannin and phytic acid in sorghum flour. Production of sorghum flour was done by four treatments in triplo i.e control (without fermentation), liquid fermentation (with L. plantarum and S. cerevisiae), solid fermentation (with R. oligosporus), mixture of solid and liquid fermentation (with R. oligosporus, L . plantarum and S. cerevisiae). Analysis levels of tannin and phytic acid in sorghum flour fermentation was performed by using spectrophotometry technique. The results showed that the fermentation process was able to reduce levels of tannin from 29.13 to 33.69% and phytic acid levels from 13.36% to 44.65% on sorghum flour. The highest reduction levels of tannin and phytic acid was produced in mixture of solid and liquid fermentation 33.69% and 44.65% respectively. Reduction levels of tannin and phytic acid can be caused of tannase and phytase enzyme which produced by the microbes during the fermentation processes.